Pemanfaatan Limbah Kulit Pisang dan Kulit Nanas sebagai Bahan Baku Pembuatan Pupuk Organic Cair (POC): Utilization of Waste Banana Peel and Pineapple Peel as Raw Material for Making Liquid Organic Fertilizer (POC) - Nisa, Khoerun; Rizkyani, Ade; Firdaus Ivana, Choirunnisa; Dwi Puspita, Anggita; Kristiningsih, Ari (Journal of Sustainable Research In Management of Agroindustry (SURIMI), 2024)
Organic fertilizers are defined as fertilizers derived from plants or animals that have gone through an engineering process to improve soil biological, physical, and chemical properties. Organic fertilizers in this study were made from basic ingredients in the form of waste banana peels and pineapple peels. Pineapple and banana peels are often found in the form of waste from food and beverage processing facilities that are collected and not used. Therefore, in this study we made liquid organic fertilizer (POC) from banana and pineapple peel waste. The purpose of this study was to examine the quality of liquid organic fertilizer (POC) products with parameters of pH, temperature, and C-Organic content compared with quality standards according to the Decree of the Minister of Agriculture of the Republic of Indonesia No. 261 / KPTS / SR.310 / M / 4/ 2019 concerning Minimum Technical Requirements for Organic Fertilizers, Biological Fertilizers and Soil Improvements. The production of POC in this study was carried out using the anaerobic method, where the fermentation process itself was carried out for 14 days using Effective Microorganisms (EM4) as a bioactivator. The results of this study indicate that the highest temperature in POC made from banana peels was obtained during the initial fermentation time of 33 oC and the lowest temperature was obtained during the 3-day fermentation time of 25 oC, while in POC made from pineapple peel, the highest temperature was obtained during the initial fermentation time. of 33.5 oC and the lowest temperature was obtained during the 9-day fermentation time of 26 oC. The initial pH value for POC made from banana peels is 5 and the final pH is 4. While for POC pineapple peel, the initial pH value is 3 and the final pH is 4. For the C-Organic content in the initial POC peel the results are 0.095% and final C-Organic content of 0.021%. Meanwhile, the initial C-Organic content in the POC of pineapple peel was 0.037% and the final C-Organic content was 0.013%. The final value of the pH parameter is in accordance with the quality standard, which is 4-9 for pH, while the final value of the C-Organic parameter is not in accordance with the quality standard where the C-Organic content according to the quality standard is a minimum of 10%.